Generator of microelectric power plants for low-potential watercourses - R. N. Khamitov; R. V. Kuzmin; A. S. Meshkov; V. I. Susdorf; K. G. Pivovarov (Омский научный вестник)
The development of autonomous power supply systems based on micro-hydroelectric power plants using the energy of small watercourses is associated with the fulfillment of a number of contradictory requirements. The source should be fairly simple and cheap. A promising direction in the construction of such sources that ensure the fulfillment of these requirements is the creation of electric energy generation systems based on a generator whose inductor is combined with a hydraulic turbine. The article is devoted to the issues of designing and ensuring high performance characteristics of such micro-hydroelectric power plants.